The implementation of al-amr bi al-maa’ruf wa an-nahy al-munkar in Malaysia: a special reference to the roles of Religious Enforcement Division - Wan Muhammad, Ramizah; Abdul Salam, Khairunnasriah (2016)
This paper is to discuss about the functions of Religious Enforcement Division at the State Religious Department in Malaysia in curbing any immoral activities as well as any syariah related crimes in Malaysia. In each division there will be Religious Enforcement Officers whose role are to warn the potential offenders and also to arrest anyone who have violated the Islamic rules which have been incorporated in the Islamic enactments. The primary objective of the establishment of the division as well as the department is to make sure that the sanctity of Islamic religion is protected and the Muslims are free from any immoral activities. This is in line with the theme of the conference that Islam is the catalyst for a peaceful environment in the Malay world. Prior to the Dutch and British colonisation, Islamic law is the law of the land in Tanah Melayu and Islamic law also was codified into a code or digest and implemented in Tanah Melayu including Malacca, Pahang, Terengganu and other states. Each state in Malaysia has their own history in establishing the department in which the names are also different. For example in Kelantan, originally the name of the "department" was Office of Prohibiting Vice for the purpose of preventing any ma'siyah occurs in the state of Kelantan. The types of immoral activities will also be highlighted together with court cases. The second part of this paper is on the current developments in the Division and the issues concerned between the Division and the Department as well as the challenges that the division is facing in the course of protecting Islam and Muslim's faith in Malaysia. Islam is a religion which is beneficial to the society at large. However, if the religion was not properly administered and adequately informed to the public, it could create bad impression among the public to the religion.